Production and marketing of cassava flour for human consumption: Phase II or pilot project phase : Semesterly report - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1990)
Background information is given on a collaborative project carried out by CIAT, the Univ. del Valle, and the Colombian Integrated Rural Development Fund (DRI), which seeks to integrate the production, processing, and marketing components of the CF system under real socioeconomic conditions of a cassava growing region. Activities executed during the 2nd semester of 1989 are indicated, namely pilot plant establishment (site selection, construction, operation), development of cassava production through the establishment of 23 ha of cassava in association with maize or yams, market development using a 3-stage market research plan which yielded a list of food categories where there is potential of substituting wheat, rice, and maize flours with CF. Research support was provide with product development (manjarblanco) and improvement of processing equipment (root washer, coupling of washing and chipping machines, chipping machine). Cyanide elimination studies were also conducted and a model was developed to estimate the financial rate of return of the cassava chip plant at Chinu. (CIAT)